Investment opportunities: Hydrogen production or BTC mining?. (29th January 2022) - Ghaebi Panah, Payam; Bornapour, Mosayeb; Cui, Xiaoti; Guerrero, Josep M.
Abstract: Green hydrogen production investment is encouraged for GHG reduction while cryptocurrency mining might be more lucrative. GHG emission reduction may visibly happen in areas of attention while other dirty businesses can grow in the shadow due to inconsistent carbon policies. This paper sheds light on the importance of integrated regulatory policies among cross markets to nail a tangible global impact on GHG emissions. The levelized cost of hydrogen production via grid-connected electrolysis is calculated at around 4 €/kgH2 in Europe. The scenario-based analyses on the current markets indicate that investments in the water-splitting industries can be as attractive as BTC mining if the products are fully purchased at prices above 20 €/kgH2. Such a deep economic chasm can be moderated by policymakers. Crypto Tax is introduced to interconnect the purchased price of hydrogen with the BTC market by tagging the coins regarding the mining origins. Cryptocurrency miners are obliged to provide dynamic subsidies for electrolyzers depending on their emission coefficients and the coin prices. Simulations confirm that the crypto tax leaves insignificant impacts when BTC falls below 10, 000; however, cryptocurrency rushes, like in 2020–2021, can be harnessed in favor of green hydrogen production. The efficacy of crypto tax is also showcased by Net Present Value (NPV) trajectories for BTC soaring up to 100, 000. Highlights: Comparative profitability analysis of water electrolysis and BTC mining. Marginal and attractive price estimations for green hydrogen production in Europe. Crypto tax introduction to interconnect BTC and hydrogen markets. Interception of NPV planes for projected BTC prices.